Ultrassonography in PEEP Titration for Patients with ARDS: A narrative review (Research, Society and Development, 2023)
This study aims to verify, through a narrative review, the importance of lung ultrasound in choosing the ideal Positive End-Expiratory Pressure (PEEP) in patients with Acute Respiratory Distress Syndrome (ARDS). Accurately determining the appropriate PEEP level is essential to optimize ARDS management, balancing lung recruitment and improving oxygenation without causing adverse effects. The article explores the role of lung ultrasound in dynamic visualization of lung structures, allowing real-time assessment of lung conditions. Furthermore, methods for determining PEEP and the correlation between lung ultrasound and computed tomography in the assessment of lung aeration are discussed. Based on the available evidence, this review suggests that lung ultrasound is an incipient tool to guide the choice of PEEP in patients with ARDS, contributing to a more personalized and effective approach to treating these patients. But due to few studies carried out to date multicenter and randomized studies, research must be carried out.